PENGEMBANGAN MODEL PEMBELAJARAN MEMBACA BERBASIS STRATEGI METAKOGNITIF PQ4R DI SEKOLAH MENENGAH PERTAMA - Sarimanah, Eri (Parameter, 2015)
In general, this research aims to develop learning model of learning based on metacognitive strategy PG4R. This Research aims especially to: 1) know about objective condition on learning to read in Junior High School; 2) find learning model of reading based on metacognitive strategy PQ4R which needs Junior High School teacher; 3) find plan and model design in reading learning based on metacognitive strategy PQ4R which decent to used in Junior High School student; 4) know feasible learning model of reading based on metacognitive strategy PQ4R from the experts point of view; and 5) know the effectivity on learning model of reading based on metacognitive strategy PQ4R which is developed. The method uses research and development with qualitative and quantitative approaches. The results show that development design on learning model of reading based on metacognitive strategy PQ4R can improve students’ skill to understand reading material from comprehension in literal, inferential, evaluative, and apresuative. Learning achievement is better than reading learning which conducted by teacher without using metacognitive strategy PQ4R. The research shown by calculation results t-test is 5,975. That scores higher than t-tabel is 1,67.